Antibiotic Treatment of Dogs and Cats during Pregnancy - Marcela Rebuelto; María Elena Loza (Veterinary Medicine International)
The use of pharmacological agents in pregnant females poses a major clinical challenge due to the marked physiological changes that may modify the pharmacokinetics of drugs and to the potential effects on the fetus. The purpose of this paper is to review briefly our knowledge on the use of antibacterial drugs during pregnancy and to provide information for the judicious selection of an antimicrobial treatment for use in pregnant bitches and queens. The risk to the fetus is a result of the ability of a drug to reach the fetal circulation and to produce toxic effects. The placenta functions as a barrier that protects the fetus due to the presence of transporters and metabolising enzymes; however, during pregnancy, the presence and activity of both enzymes and transporters may change. Antimicrobial agents that have been shown to be safe for use during pregnancy include betalactams, macrolides, and lincosamides. Pharmacotherapy during pregnancy in all species may affect adversely the developing fetus; therefore, it should be avoided when possible.